Pengaruh Nilai Pelanggan, Kualitas Pelayanan, dan Kedekatan Emosional Terhadap Loyalitas Pelanggan (Studi Kasus pada Koperasi Simpan Pinjam Pratama Surya Makmur) - Tiragiajeng Fandira; Imam Baidlowi; Toto Heru Dwihandoko (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Savings and loan cooperatives are non-bank financial institutions engaged in the business of accepting deposits and lending to their members in the smallest possible amount. The Pratama Surya Makmur Savings and Loans Cooperative is a service institution that can survive in the midst of industrial competition by prioritizing customer loyalty. The purpose of this research is to analyze the influence of customer value, service quality and emotional closeness to determine the extent to which customer loyalty is owned partially and simultaneously. This study used a quantitative approach and the results of distributing questionnaires as the main data source. Using a purposive sampling method which produces 85 respondents. The data analysis technique used is multiple linear regression analysis using IBM SPSS version 22. The results of this study indicate that the customer value variable has a positive and significant effect on customer loyalty. The service quality variable has a positive and significant effect on customer loyalty. The emotional closeness variable has a positive and significant effect on customer loyalty. The variables of customer value, service quality and emotional closeness also have a positive and significant effect on customer loyalty of the Mojokerto The Pratama Surya Makmur Savings and Loans Cooperative